Optimization of Cone Media in Improving Football Dribbling Skills of Grade V Students of UPT SDF SD Inperes Karunrung - Muhammad Faiz Mahdi Jaya; Alivia Adilla; Muflihuddin Ismail; Andi Muhammad Arsil Hasyim; Muhammad Fauzan Pratama (Jurnal Jejak Edukasi (JJE), 2025)
Introduction. Dribbling skills are an essential fundamental ability in football, especially for elementary school students who are in the stage of developing motor coordination. However, observations indicate that many fifth-grade students at UPT SD Inpres Karunrung still experience difficulties in controlling the ball. To address this issue, cone media is used as a simple, engaging, and effective training aid to improve dribbling skills. Methods. This study employed an experimental method with a one-group pre-test post-test design. The research subjects were fifth-grade students participating in physical education learning. The research instrument consisted of a dribbling skill test assessing speed, accuracy, and ball control. Data were obtained through measurements conducted before (pre-test) and after (post-test) dribbling training using cone media over several sessions. Data analysis was performed using statistical tests to determine differences between the results before and after the treatment. Results. The findings show an improvement in dribbling skills after the use of cone media. In terms of speed, the average time decreased from 10.48 ± 2.15 seconds to 10.07 ± 2.01 seconds (∆ = 0.41 seconds, p = 0.448). In terms of accuracy, the score increased from 2.7 ± 0.67 to 3.5 ± 0.70 (∆ = 0.8, p = 0.408). Meanwhile, in ball control, the score increased from 2.6 ± 0.48 to 3.4 ± 0.51 (∆ = 0.8, p = 0.301). Although the p-values do not indicate statistically significant differences, the changes in mean values for the three variables… The variable describes an improvement in students’ dribbling skills after participating in training using cone-based media. Conclusion. Cone media is effective as a learning aid for improving the dribbling skills of fifth-grade students at UPT SPF SD Inpres Karunrung. Improvements in speed, accuracy, and ball control indicate that simple media such as cones can serve as an innovative, engaging, and easily implemented alternative learning method in physical education. Conclusion. Cone media is effective as a learning aid for improving the dribbling skills of fifth-grade students at UPT SPF SD Inpres Karunrung. Improvements in speed, accuracy, and ball control indicate that simple media such as cones can serve as an innovative, engaging, and easily implemented alternative learning method in physical education.